Characterization of Rare Earth Elements Enrichment Based on Coal Calorific Value Variations - Yudi Arista Yulanda; Wahyudi Zahar; Muhammad El Hakim; Jarot Wiratama; Putri Abby Larassati (Jurnal Ilmiah Dinamika Rekayasa, 2026)
The accelerated transition toward clean energy has triggered a global surge in demand for Rare Earth Elements (REEs), while its supply chain remains heavily dependent on a single dominant producing nation. This constraint has compelled extensive exploration into alternative REEs feedstocks, particularly within coal deposits and Coal Combustion Residuals (CCRs) or Fly Ash and Bottom Ash (FABA). Although multiple studies on REEs occurrences within coal seams and FABA have been conducted, research directly correlating the influence of coal calorific value to REEs enrichment remains profoundly limited. This study addresses this critical research gap by analyzing the correlation between coal energy quality (calorific value) and REEs occurrences within the Oligocene Sinamar Formation at the PT Kuansing Inti Makmur concession area. The methodology integrated ASTM standard proximate analysis to determine fundamental coal quality parameters and Inductively Coupled Plasma-Optical Emission Spectroscopy (ICP-OES) to quantify the concentrations of 10 targeted REEs elements. The proximate results indicated that sample KS100 exhibits a high ash yield (24.11% AR) with a lower gross calorific value (3,560 kcal/kg AR). Conversely, sample KS300 is characterized by a lower ash content (10.36% AR) and a higher calorific value (4,866 kcal/kg AR). Crucially, the ICP-OES analytical data revealed a compelling trend: REEs enrichment is notably more pronounced in the higher-energy quality coal seam (KS300). Cerium (Ce) and Lanthanum (La) emerged as the most dominant Light Rare Earth Elements (LREEs) in both horizons, with Ce concentrations reaching 114 ppm in KS100 and 150 ppm in KS300. Highly strategic elements essential for permanent magnet motors in electric vehicles, such as Neodymium (Nd), reached 91.76 ppm in KS300, which is nearly double the 50.51 ppm recorded in KS100. Furthermore, the total REEs concentration within the macroscopic parting layer was significantly lower (180.01 ppm) compared to the dispersed inorganic fraction within the coal matrices themselves. In conclusion, the novelty of this research demonstrates that REEs enrichment does not correlate linearly with the degradation of calorific value or total ash yield. Instead, it is suggested to be influenced by specific geological settings and the geochemical dynamics at the adjacent claystone boundaries.